Cholinergic Control of Information Coding. Issue 9 (September 2017) - van Kempen, Jochem; Panzeri, Stefano; Thiele, Alexander
Abstract : Specific forms of firing rate correlations can limit efficient information coding in neuronal populations. How this is mitigated is an important topic of current research. A novel study shows that increasing cortical acetylcholine (ACh) levels alter specific aspects of the population correlation structure, which in turn improves population-coding abilities.